130k views
2 votes
And it's not f'(x) = (0.1x - 1)^2 + 1)

And it's not f'(x) = (0.1x - 1)^2 + 1)-example-1

2 Answers

3 votes
I’m pretty sure the answer is A
User Brugner
by
4.7k points
3 votes

Answer:

A

Explanation:

To reflect a function over the x-axis, we multiply the function by -1. So, if f(x) is the original function, then -f(x) is the function across the x-axis.

To reflect a function over the y-axis, we multiply the inside of the function by -1. So, if f(x) is the original function, then f(-x) is the function across the x-axis.

We have:


f(x)=(x-1)^2+1

Then:


f(-x)=(-x-1)^2+1=f ^\prime(x)

We can see that the choice that resembles this is A. If we let:


f(-4x)=(-4x-1)^2+1

This is a reflection over the y-axis followed by a horizontal compression by a factor of 4.

Hence, our answer is A.

User Viira
by
4.9k points